A narrative case study of Indonesian EFL learners’ identities - Wirza, Yanty (Universitas Pendidikan Indonesia, 2018)
Much research on identity (re)construction in periphery countries (e.g., Pakistan, Thailand) continues to shed light on how English learners negotiate and construct their identities. This narrative case study explores how two Indonesian learners of English who have been learning English for many years reflect on their journey of identity construction as English learners in their local contexts. Nested in a narrative inquiry methodology, this study examined the participants’ personal stories that were unique, rich and nuanced with the interplay of social, cultural and political dimensions (re)shaping their experiences. The initial phases of identity construction revealed from the participants’ early years indicated that the emergence of identity as English learners was largely marked by a false or negative association of the English language in relation to various aspects of being a school subject leading to a false sense of positive identity. Pedagogical implications of the study are also presented in this article.